Tata Kelola Perusahaan Dalam Mengurangi Kecurangan Laporan Keuangan (Systematic Literature Review Dengan Metode Meta Sintesis) - Andreas Tanjaya; Febrian Kwarto (Universitas Muhammadiyah Malang, 2022)
Financial statement fraud is an opportunistic behavior of agents that misleads the principal due to information asymmetry. Principals take advantage of corporate governance to overcome this. Corporate governance is supervisory mechanisms carried out by principals against agents that aim to reduce information asymmetry. This study aims to identify the corporate governance structure and understand the role of corporate governance in reducing the potential for fraudulent financial statements. This research is a systematic literature review with a meta-synthesis method using a meta-aggregation approach. We identify six components of the corporate governance structure: the government, investors, the board of directors, management, whistleblowing systems, and auditors. Our research has not found the role of any of the components that can effectively reduce the potential for fraudulent financial statements. These components need to collaborate and synergize regarding reducing fraudulent financial statements. Our research also identifies several factors that can influence corporate governance